Evaluation on physico-chemical properties of pink guava puree residue as bioresource - Mhd Abd Kader, K. A.; Ab. Aziz, Norashikin; Aziz, A.; Talib, A. T.; Ahmad, N. H.; Tan, C. P.; Kamarudin, S. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
Pink Guava Puree (PGP) factory produces tons of residues from its unit operation [refiner (R), siever (S), and decanter (D)]. These residues represent a waste of nutrients and can contribute to environmental problem. However, it can benefit related industries if the properties of the residues are known. Thus, this research aims to determine the compositions of the residues from PGP processing factory in order to evaluate possible value-added by-product and energy sources. The residues from each unit operation were being tested for proximate composition, dietary fibre components, pH value, emulsifying activity (EA) and emulsifying stability (ES), carbon-to-nitrogen (C/N) ratio, and sugar analysis. The sugar content was analysed using High Performance Liquid Chromatography (HPLC-RI detector). Results showed that the residues have good composition of carbohydrate (11.82–12.18%), and thus potential as carbon source and can be a good substrate for fermentation. These residues may also benefit the food industry as a good source of dietary fibre (18.63–29.86%). The pH value for these PGP residues is 4; thus they were considered as acidic food by-product. The low pH value also contributed to the low EA and ES value other than the low content of protein in the sample. C/N ratio for PGP residue from R (46:1) is the lowest compared to the C/N ratio from S (84:1) and D (115:1). The amount of sugars detected in the PGP residues in descending order were fructose > glucose > sucrose.